Brand Equity, Service Quality, and Price on Fast Food Purchase Decisions in Sidoarjo: Ekuitas Merek, Kualitas Pelayanan, dan Harga Terhadap Keputusan Pembelian Makanan Cepat Saji di Sidoarjo - Putri, Novithalya Bella Tiara; Indayani, Lilik (Indonesian Journal of Innovation Studies, 2023)
The type of research used in this research is quantitative research with associative explanatory method, where this associative relationship is used to determine the relationship between two or more variables that are shown in a causal relationship or cause and effect. ). The samples taken in this study were Hisana Fried Chicken consumers in Sidoarjo who had visited and bought 100 respondents. Based on the Simultaneous F test, the value of sig = 0.00 and the value of = 0.05 means that P < then H0 is rejected, meaning that there is an influence of brand equity, service quality and prices on the purchasing decisions of Hisana Fried Chicken in Sidoarjo, It is expected that respondents will pay more attention and consider in making purchases of goods and services so as to further increase the effectiveness of purchases and consumer convenience.